Physical activity-related indicators in children and adolescents in Uruguay: A scoping review based on the Global Matrix initiative - Bizzozero-Peroni, Bruno; Fernández-Giménez, Sofía; Pintos-Toledo, Enrique; Corvos, César Augusto; Díaz-Goñi, Valentina; Brazo-Sayavera, Javier (Frontiers in Public Health, 2022)
Background: The first Uruguay's Report Card in 2018 based on the Global Matrix initiative showed the lack of information on physical activity in children and adolescents. This study mapped and examined the available evidence on physical activity-related indicators based on Uruguay's 2022 Report Card. Methods: The scoping review was reported using the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews extension for Scoping Reviews guidelines. A comprehensive literature search was performed for the period between 2018 and 2021 including electronic databases (PubMed, Web of Science, LILACS, Scielo and Latindex), grey literature (Google Scholar, open access thesis, relevant websites of State-agencies and International Organizations), national and regional relevant journals, and reference lists of key texts. Both the selection and data-charting process were conducted independently by two researchers. Data items from each paper were charted based on the Population, Concept and Context elements reflected in the objective of the review. A narrative synthesis and network plots were conducted to summarise the evidence. Results: A total of 20 papers and reports were included in this review, consisting of 4 peer-reviewed scientific papers, 3 bachelor's theses, 4 official documents of State-agencies, 4 Government reports of which 3 included national surveys, and 5 laws. Strengths, weaknesses, and knowledge gaps were identified from the evidence. We synthesised main challenges such as publishing scientific studies, establishing cross-national and cross-sectoral collaborations in research projects, generating high-quality data, reporting information on social inequality indicators that influence equitable distribution, or increasing access to public information. Our results support early emerging and growth research on this topic. However, despite existing studies on physical activity-related indicators in the Uruguayan youths, lack of high-quality evidence remains clear. Conclusions: The findings of this scoping review provide the best available evidence for identifying and overcoming the challenges of physical activity-related indicators research in Uruguay. The methodological framework used could be useful for countries involved in future editions of the Global Matrix initiative. Protocol registration: Open Science Framework, https://osf.io/hstbd/